Edukasi Masa Depanku, Pilihanku: Menumbuhkan Growth Mindset dan Kesadaran Bijak dalam Menghindari Pernikahan Dini pada MA Daarul Hasan Desa Cihawuk: Pengabdian - Dzulfikar Maulana Rahadian PM; Sani Asmi Ramdani Lestari; Allysa Angraeni; Syifa Abdillah; Alfani Yunisa; Rofita Alya Puspita Sari; Regitha Anggraeni Koswara Putri; Muhammad Hamiz Al-Qowiyy; Luthfi Roja Wirawan; Dinda Thalia Trianita Putri; Muhammad Rafi Ghani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Early marriage remains a worrying social issue in Indonesia, especially among teenagers. Cihawuk Village, Bandung Regency, is one of the areas with a high tendency of early marriage due to educational, economic, cultural, family, and promiscuity factors. A community service program entitled